OPTIMASI PEMBUATAN PADA USAHA UMKM KERIPIK KELADI - Mboni, La; Safitri, Wulandari; Wader, Elisabeth J; Pinontoan, Monika; Wahyudien, Mohammad Arief Nur (Industrial Engineering Journal – System, 2023)
MSMEs play an important role in driving the economy, even though they are small scale, thesebusinesses are able to help the wheels of a country's economy. MSMEs are a large and diversesector, and their contribution to economic growth and job creation is very significant. One of thepopular MSME sectors is the snack food industry, including the production of taro chips. Theobstacle in running this MSME is that it only looks at previous demand without using a productionplanning strategy. The non-implementation of production planning strategies is motivated byvarious factors. In this research, we will discuss the optimal production amount for Keladi ChipsMSMEs so that profits can be maximized by using the Linear Programming method. The datarequired to use the Linear Programming method is collecting data such as product type, productyield data, number of working days data, and sales data. This research produces a monthlyproduction profit of Rp. 7,584,000 of them with a production output of taro chips products of 900packs in one month.